Age of Choice or Diversification? Brazil, Portugal, and Capacity-Building in the Angolan Armed Forces. Issue 3 (3rd July 2018) - Seabra, Pedro; Abdenur, Adriana Erthal
ABSTRACT: The role of South–South cooperation in peace and security has prompted new questions about how, and to what extent, these ties differ from responses implemented by traditional donor countries. However, little of this literature has taken a directly comparative approach, and few studies exist on the role of such cooperation ties in the security domain. This article helps to fill these gaps by contrasting the roles of Portugal and Brazil in capacity-building of the Angolan Armed Forces. Portugal has long held a central role in this domain. However, that centrality has been increasingly challenged by emerging South–South defense cooperation players that claim to offer different approaches. Brazil, in particular, made considerable inroads with Angola in recent years. How has Brazil engaged with the Angolan military, and how does its approach to compare with that of Portugal? We focus on the case study of the Angolan Navy against the backdrop of emerging maritime security issues while addressing the question of whether or not rising powers can break the restricted club of external security providers in Africa.